Resistance and alternatives to globalization in Latin America and the Caribbean - Harris, Richard L. (2002)
Examines the extent to which the neoliberal stabilization and structural reforms undertaken by most of the governments in the region to integrate their economies into the global capitalist economy have met with a wide range of popular resistance. Describes the formation and first two annual meetings of the World Social Forum. Discusses the urgent need to mobilize broad-based popular support for one or more politically viable alternatives to the prevailing neoliberal project, laying out some of the prerequisities for a viable alternative strategy.